Hospitalizations and deaths from femoral fractures in Brazil, with emphasis on the State of Pará between 2010 and 2020 (Research, Society and Development, 2023)
Introduction: The femur is the longest and most voluminous bone in the human body, located in the thigh. Its upper end articulates with the pelvis, forming the hip joint, allowing for extension, flexion, and rotation movements. The proximal region of the femur is particularly susceptible to fractures, being considered one of the most common areas for this type of bone injury. Objective: This study aimed to understand the epidemiological character of hospitalizations for this fracture in the Brazilian population, with a focus on the state of Pará. This is an ecological study that used data from the Hospital Information System (SIH/SUS) to analyze individuals who were hospitalized in the Brazilian Unified Health System (SUS) due to femur fractures between January 2010 and December 2020. Results: Pará has the highest number of hospitalizations and deaths from femur fractures. The Metropolitan Region I, composed of Belém and Ananindeua, concentrates the majority of hospitalizations and deaths related to this type of fracture. The age group with the highest number of hospitalizations and deaths is above 80 years old. Hospitalization is more frequent among men, but the number of deaths occurs in a 1:1 ratio. Additionally, the municipality of Ananindeua has the highest number of deaths, followed by Belém. Conclusion: It is crucial to plan effective fall prevention measures in order to reduce the number of hospitalizations and deaths from femur fractures in the state of Pará.